Corporate Performance and Stakeholder Management: Balancing Shareholder and Customer Interests in The U.K. Privatized Water Industry - Ogden, Stuart; Watson, Robert (Academy of Management Journal, 1999)
This study examined a major contention of stakeholder theory: namely, that a firm can simultaneously enhance the interests of its shareholders and other relevant stakeholders. Financial data relating to the U.K. water supply industry and the customer service performance indicators introduced after privatization in 1989 to protect customer interests provided the basis of our empirical analysis. The results show that, although improving relative customer service performance is costly for firms in terms of current profits, shareholder returns respond in a significantly positive manner to such improvements. We interpret this finding as being consistent with stakeholder theory.